\left\{ \begin{array} { l } { ( x + 10 ) ( y + 3 ) = + 500 + x y } \\ { ( x - 15 ) ( y - 9 ) = x y + ( - 600 ) } \end{array} \right.
Solve for x, y
x = \frac{20}{3} = 6\frac{2}{3} \approx 6.666666667
y=45
Graph
Share
Copied to clipboard
xy+3x+10y+30=500+xy
Consider the first equation. Use the distributive property to multiply x+10 by y+3.
xy+3x+10y+30-xy=500
Subtract xy from both sides.
3x+10y+30=500
Combine xy and -xy to get 0.
3x+10y=500-30
Subtract 30 from both sides.
3x+10y=470
Subtract 30 from 500 to get 470.
xy-9x-15y+135=xy-600
Consider the second equation. Use the distributive property to multiply x-15 by y-9.
xy-9x-15y+135-xy=-600
Subtract xy from both sides.
-9x-15y+135=-600
Combine xy and -xy to get 0.
-9x-15y=-600-135
Subtract 135 from both sides.
-9x-15y=-735
Subtract 135 from -600 to get -735.
3x+10y=470,-9x-15y=-735
To solve a pair of equations using substitution, first solve one of the equations for one of the variables. Then substitute the result for that variable in the other equation.
3x+10y=470
Choose one of the equations and solve it for x by isolating x on the left hand side of the equal sign.
3x=-10y+470
Subtract 10y from both sides of the equation.
x=\frac{1}{3}\left(-10y+470\right)
Divide both sides by 3.
x=-\frac{10}{3}y+\frac{470}{3}
Multiply \frac{1}{3} times -10y+470.
-9\left(-\frac{10}{3}y+\frac{470}{3}\right)-15y=-735
Substitute \frac{-10y+470}{3} for x in the other equation, -9x-15y=-735.
30y-1410-15y=-735
Multiply -9 times \frac{-10y+470}{3}.
15y-1410=-735
Add 30y to -15y.
15y=675
Add 1410 to both sides of the equation.
y=45
Divide both sides by 15.
x=-\frac{10}{3}\times 45+\frac{470}{3}
Substitute 45 for y in x=-\frac{10}{3}y+\frac{470}{3}. Because the resulting equation contains only one variable, you can solve for x directly.
x=-150+\frac{470}{3}
Multiply -\frac{10}{3} times 45.
x=\frac{20}{3}
Add \frac{470}{3} to -150.
x=\frac{20}{3},y=45
The system is now solved.
xy+3x+10y+30=500+xy
Consider the first equation. Use the distributive property to multiply x+10 by y+3.
xy+3x+10y+30-xy=500
Subtract xy from both sides.
3x+10y+30=500
Combine xy and -xy to get 0.
3x+10y=500-30
Subtract 30 from both sides.
3x+10y=470
Subtract 30 from 500 to get 470.
xy-9x-15y+135=xy-600
Consider the second equation. Use the distributive property to multiply x-15 by y-9.
xy-9x-15y+135-xy=-600
Subtract xy from both sides.
-9x-15y+135=-600
Combine xy and -xy to get 0.
-9x-15y=-600-135
Subtract 135 from both sides.
-9x-15y=-735
Subtract 135 from -600 to get -735.
3x+10y=470,-9x-15y=-735
Put the equations in standard form and then use matrices to solve the system of equations.
\left(\begin{matrix}3&10\\-9&-15\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}470\\-735\end{matrix}\right)
Write the equations in matrix form.
inverse(\left(\begin{matrix}3&10\\-9&-15\end{matrix}\right))\left(\begin{matrix}3&10\\-9&-15\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}3&10\\-9&-15\end{matrix}\right))\left(\begin{matrix}470\\-735\end{matrix}\right)
Left multiply the equation by the inverse matrix of \left(\begin{matrix}3&10\\-9&-15\end{matrix}\right).
\left(\begin{matrix}1&0\\0&1\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}3&10\\-9&-15\end{matrix}\right))\left(\begin{matrix}470\\-735\end{matrix}\right)
The product of a matrix and its inverse is the identity matrix.
\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}3&10\\-9&-15\end{matrix}\right))\left(\begin{matrix}470\\-735\end{matrix}\right)
Multiply the matrices on the left hand side of the equal sign.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}-\frac{15}{3\left(-15\right)-10\left(-9\right)}&-\frac{10}{3\left(-15\right)-10\left(-9\right)}\\-\frac{-9}{3\left(-15\right)-10\left(-9\right)}&\frac{3}{3\left(-15\right)-10\left(-9\right)}\end{matrix}\right)\left(\begin{matrix}470\\-735\end{matrix}\right)
For the 2\times 2 matrix \left(\begin{matrix}a&b\\c&d\end{matrix}\right), the inverse matrix is \left(\begin{matrix}\frac{d}{ad-bc}&\frac{-b}{ad-bc}\\\frac{-c}{ad-bc}&\frac{a}{ad-bc}\end{matrix}\right), so the matrix equation can be rewritten as a matrix multiplication problem.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}-\frac{1}{3}&-\frac{2}{9}\\\frac{1}{5}&\frac{1}{15}\end{matrix}\right)\left(\begin{matrix}470\\-735\end{matrix}\right)
Do the arithmetic.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}-\frac{1}{3}\times 470-\frac{2}{9}\left(-735\right)\\\frac{1}{5}\times 470+\frac{1}{15}\left(-735\right)\end{matrix}\right)
Multiply the matrices.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}\frac{20}{3}\\45\end{matrix}\right)
Do the arithmetic.
x=\frac{20}{3},y=45
Extract the matrix elements x and y.
xy+3x+10y+30=500+xy
Consider the first equation. Use the distributive property to multiply x+10 by y+3.
xy+3x+10y+30-xy=500
Subtract xy from both sides.
3x+10y+30=500
Combine xy and -xy to get 0.
3x+10y=500-30
Subtract 30 from both sides.
3x+10y=470
Subtract 30 from 500 to get 470.
xy-9x-15y+135=xy-600
Consider the second equation. Use the distributive property to multiply x-15 by y-9.
xy-9x-15y+135-xy=-600
Subtract xy from both sides.
-9x-15y+135=-600
Combine xy and -xy to get 0.
-9x-15y=-600-135
Subtract 135 from both sides.
-9x-15y=-735
Subtract 135 from -600 to get -735.
3x+10y=470,-9x-15y=-735
In order to solve by elimination, coefficients of one of the variables must be the same in both equations so that the variable will cancel out when one equation is subtracted from the other.
-9\times 3x-9\times 10y=-9\times 470,3\left(-9\right)x+3\left(-15\right)y=3\left(-735\right)
To make 3x and -9x equal, multiply all terms on each side of the first equation by -9 and all terms on each side of the second by 3.
-27x-90y=-4230,-27x-45y=-2205
Simplify.
-27x+27x-90y+45y=-4230+2205
Subtract -27x-45y=-2205 from -27x-90y=-4230 by subtracting like terms on each side of the equal sign.
-90y+45y=-4230+2205
Add -27x to 27x. Terms -27x and 27x cancel out, leaving an equation with only one variable that can be solved.
-45y=-4230+2205
Add -90y to 45y.
-45y=-2025
Add -4230 to 2205.
y=45
Divide both sides by -45.
-9x-15\times 45=-735
Substitute 45 for y in -9x-15y=-735. Because the resulting equation contains only one variable, you can solve for x directly.
-9x-675=-735
Multiply -15 times 45.
-9x=-60
Add 675 to both sides of the equation.
x=\frac{20}{3}
Divide both sides by -9.
x=\frac{20}{3},y=45
The system is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}